2018
DOI: 10.1016/j.agee.2017.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of transference of inoculation-related technologies: A case study of evaluation of soybean rhizobial strains under the agro-climatic conditions of Brazil and Mozambique

Abstract: HighlightsSoybean N demand can be fulfilled by biological nitrogen fixation (BNF).Bradyrhizobium strains from Brazil and USA were tested in Brazil and Mozambique.Inoculation resulted in grain yield gains of 4–5% in Brazil and 20–29% in Mozambique.Transference of BNF technologies is feasible, speeding up the production system.Exotic soybean Bradyrhizobium strains can highly benefit soybean in Mozambique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 57 publications
3
15
0
Order By: Relevance
“…This study also revealed differences among strains in both nodulation and shoot dry weight improvement which is primarily due to their genetic differences. Other studies conducted in Africa have similarly reported consistent variation in symbiotic effectiveness among indigenous rhizobia strains (Abaidoo et al, 2007;Chibeba et al, 2017Chibeba et al, , 2018 and consequently this study further contributes to the evidence that effective rhizobia do occur in African soils.…”
Section: Effectiveness Of Indigenous Strains Under Controlled Environsupporting
confidence: 77%
See 3 more Smart Citations
“…This study also revealed differences among strains in both nodulation and shoot dry weight improvement which is primarily due to their genetic differences. Other studies conducted in Africa have similarly reported consistent variation in symbiotic effectiveness among indigenous rhizobia strains (Abaidoo et al, 2007;Chibeba et al, 2017Chibeba et al, , 2018 and consequently this study further contributes to the evidence that effective rhizobia do occur in African soils.…”
Section: Effectiveness Of Indigenous Strains Under Controlled Environsupporting
confidence: 77%
“…This is as a result of the native rhizobia being less effective (Osunde et al, 2003). The same observation has been made by Chibeba et al (2018) who observed that an appreciable proportion of rhizobia population in Mozambican soils was composed of ineffective rhizobia. The N+ control produced high shoot dry weight; this is mainly as a result of the mineral N being absorbed by the plant at early stages compared to the fixed N and thus improved vegetative formation (Saturno et al, 2017).…”
Section: Effectiveness Of Indigenous Strains Under Field Conditionssupporting
confidence: 63%
See 2 more Smart Citations
“…It is important to emphasize that the meta-analysis for grain yield considered only data from field studies, in which the variables are difficult to control, such as the presence of native strains competing with the inoculant for nodulation. Furthermore, soybean responses to co-inoculation may vary according to plant genotype, bacterial strain, environmental conditions, as well as the quantity and quality of PGPR cells used as inoculants (Schmidt, Messmer & Wilbois, 2015;Pannecoucque et al, 2018;Chibeba et al, 2018). These variations in responses to co-inoculation were evident in the studies evaluated, which can be observed in the CI for different PGPR strains, in all the traits described.…”
Section: Discussionmentioning
confidence: 97%